PEMANFAATAN INSTAGRAM DALAM MEMBANGUN BRAND AWARENESS PADA @BABYMOMCAREPAKAM - Alya, Rahma; Nashrillah (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
Social media, particularly Instagram, has become a primary tool in digital marketing due to its ability to reach a wide and interactive audience. In Indonesia, Instagram is the second most popular platform, but research on its use to build brand awareness for small businesses in the mother and baby care sector is still limited. This study aims to analyze how the @babymomcarepakam account, a small business in Lubuk Pakam, utilizes Instagram to increase brand awareness. This qualitative study employs interviews with the business owner and five active followers of the @babymomcarepakam account, Instagram content observation, and analysis of posted documentation. Data was analyzed using an interactive model (reduction, presentation, and conclusion drawing), with triangulation to ensure validity. The Instagram account @babymomcarepakam utilizes educational content, Reels, Stories, and responsive communication to build brand awareness. Visual consistency and active interaction enhance brand recognition and recall among the audience, with positive responses to service quality and competitive pricing. Instagram has proven effective in increasing brand awareness through consistent and consumer-centric content strategies, aligning with Robert F. Lauterborn's Marketing Mix Theory (4C) and Chris Heuer's Social Media Management Theory. Practically, small businesses can adopt similar strategies, such as collaborating with influencers and optimizing Instagram ads, to expand their reach. Theoretically, this study enriches digital marketing literature by highlighting Instagram's role in a specific sector, encouraging further exploration of other social media platforms. Keywords: Social Media; Brand Awareness; Digital Marketing; Instagram; @babymomcarepakam.